Motivating Factors that Affect Enrolment and Student Performance in an ODL Engineering Program - Dadigamuwa, P.R.; Senanayake, Samans (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
The present study was carried out to determine the motivating factors for enrolling in an engineering study programme in open and distance learning (ODL) and the factors that affect the students’ performance. The study was conducted with two convenient samples of students following distance learning courses in engineering technology, conducted by the Open University of Sri Lanka and leading to the award of diploma or degree in Engineering Technology. One sample consisted of students who failed to qualify for sitting the year-end examination and the other consisted of successful students. The study showed that many students opt to follow the programme without knowing the relevance of the study programme for them. Most of the students (53%) had taken the courses believing that they could obtain a recognized degree. The students with secondary education qualifications in the mathematics stream were found to be successful, provided that they had selected the ODL programmes with an understanding of the nature of the ODL system, the percentages being 61 with 4 passes, 75 with 3 passes, and 20 with 2 passes at the General Certificate in Education (Advanced Level) examination. All successful students were of the opinion that the course delivery methods should be improved, especially face-to-face teaching, laboratory classes, and assignments.